Semi-parametric measures of scale characteristics of German natural gas-fired electricity generation - Stefan Seifert (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Scale characteristics are key properties of production functions that determine optimal firm sizes, and have considerable policy implications for sectors undergoing restructuring. However, estimates of scale characteristics typically vary with the assumptions of the underlying empirical model. This paper derives estimators of scale efficiency and scale elasticity for semi-parametric stochastic non-smooth envelopment of data (StoNED) that are based on few assumptions and rely neither on a functional form nor on distributional assumptions, but satisfy basic microeconomic properties. The estimators are applied to a unique sample covering 124 natural gas-fired power plants operating in Germany in 2011. Results indicate that on average plants operate under constant to slightly decreasing returns-to-scale, and scale inefficiency is found to be overall rather low. However, considerable improvement potential exists due to technical inefficiency. The results allow the strong fragmentation of gas-fired electricity generation in Germany, but emphasize the importance of using best practices on plant level.
Keywords: D24; C14; O13; L94; 330; Stochastic Non-Smooth Envelopment of Data (StoNED); Returns-to-scale; Scale Elasticities; Scale Efficiency; Gas-fired Electricity Generation; Germany